Analysis of Students' Mathematical Literacy Ability in Solving Mathematical Problems in View of Logical Intelligence - Tuti Isnani; Hendri Handoko; Saluky (Educational Insights, 2023)
Mathematical literacy skills are really needed by students in everyday life. Apart from that, students' logical intelligence still needs to be developed . Students must be equipped with logical intelligence to improve mathematical literacy skills so they can solve everyday mathematical problems. This research aims to determine students' mathematical literacy abilities in solving mathematical problems in terms of logical intelligence. This research was conducted at SMP Negeri 1 Gebang with subjects as many as 32 students in class VIII C. This research used a qualitative approach with descriptive methods . Data collection techniques in this research were a mathematical literacy ability test , a logical intelligence questionnaire and an interview guide. Logical intelligence is divided into three categories, namely high, medium and low , 1 student is taken from each category to be interviewed . The results of the research show that students' mathematical literacy abilities in solving mathematical problems in terms of high category logical intelligence can fulfill three indicators of mathematical literacy abilities . Mathematical literacy ability in solving students' mathematical problems in terms of logical intelligence in the moderate category can fulfill two indicators of mathematical literacy ability . Mathematical literacy ability in solving students' mathematical problems in terms of low category logical intelligence can fulfill two indicators of mathematical literacy ability . The average mathematical literacy ability of all categories of students' logical intelligence contains two indicators of mathematical literacy ability .